PEMBELAJARAN BAHASA INDONESIA TULIS BIPA TINGKAT PEMULA - Qurrota Akyun (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
BIPA is Indonesian for foreign speakers, a program about learning Indonesian that specifically provides language learning for foreign students. BIPA learning includes learning strategies and teaching materials that are designed according to the level and needs of foreign students. BIPA students are students who come from outside Indonesia, who study Indonesian as their first language. Foreign students learning Indonesian can learn differently from each other. Different learning abilities will determine students will be at the appropriate level of language skills. BIPA learning aims to master four aspects of language skills, one of which is writing. In BIPA learning, learning materials and strategies are designed according to the levels and needs of foreign students. Therefore, understanding of the characteristics of Indonesian written BIPA students beginner at UM needs to be mastered by the instructor.